2021 IEEE International Conference on Communications Workshops (ICC Workshops) 2021
DOI: 10.1109/iccworkshops50388.2021.9473699
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of OTFS-based Uplink Massive MIMO with ZF Receivers

Abstract: This paper considers an orthogonal time frequency space (OTFS)-based uplink massive multiple-input-multipleoutput (MIMO) system, in which all users transmit symbols to a base station (BS) that is equipped with an one-dimensional uniform linear array (ULA) in the delay-Doppler domain. The zero-forcing (ZF) decoding scheme is applied at the BS. Different from most existing OTFS works, this paper mainly focuses on the performance analysis. Furthermore, in contrast to the existing massive MIMO works, which assume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We start by presenting some characteristics of the DD domain channel representation in (8), which will facilitate the ensuing achievable rate analysis.…”
Section: Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We start by presenting some characteristics of the DD domain channel representation in (8), which will facilitate the ensuing achievable rate analysis.…”
Section: Performance Analysismentioning
confidence: 99%
“…RVs. By using (8), and noticing that channel gains of different path are zero-mean i.i.d RVs, i.e., E ĥ * pq,i ĥpq,j = 0, ∀i = j, and then applying Lemma 1 we get E x d,q 2 = ρ d…”
Section: Performance Analysismentioning
confidence: 99%
“…From Theorem 2, the key terms are the diagonal elements of the diagonal matrix Ω q,q given in (21). Looking at (21) and recalling the vector a(θ q,i ) in (2), with [15], we have…”
Section: Mn−1 V=0mentioning
confidence: 99%
“…We recall that the pulse shape functions that are commonly utilized in OTFS, vary from the ideal bi-orthogonal waveforms as defined in [6] to the more practical rectangular pulses [6]- [9]. Specifically, for the ideal bi-orthogonal pulses, [7] considered the integer delay and Doppler shift scenario. It was shown that the output signal is a linear combination of the shifted versions of the input symbols caused by the delay and Doppler taps.…”
Section: Introductionmentioning
confidence: 99%